Etika dan Sistem Keuangan Islam - Muhammad Luqman El Hakim (SALSABIL : Jurnal Syariah dan Hukum Ekonomi, 2026)
This study constructs a profound analysis of the ethical dimensions within earnings management and cooperation mechanisms (syirkah) inside the Islamic financial ecosystem. Utilizing normative analysis and content analysis methodologies, this research evaluates how Islamic ethical axioms transform materialistic orientations into blessing-based sustainability. The findings demonstrate that the implementation of Tawhid, ‘Adl, and Amanah effectively mitigates opportunistic behaviors such as earnings management in its various forms—including taking a bath and income smoothing—which have historically catalyzed systemic vulnerabilities. Furthermore, the profit-sharing paradigm facilitates the seamless integration of financial intermediation with real-sector productivity, fostering macroeconomic stability that is significantly more resilient than interest-based systems. This study concludes that strengthening ethical pillars is not merely a technical adjunct but an absolute prerequisite for global economic homeostasis.